Investigating the Relationship between Mental Health and Perceived Social Support in the Elderly referred to selected hospitals of Shahid Beheshti University of Medical Sciences in Tehran - Paknejad, Fatemeh; Mohtashami, Jamileh; Naderi, Manijeh (Technium Social Sciences Journal, 2021)
Introduction: Most elderly people are at risk of chronic diseases and their complications and problems and inadequate social support, especially among low-income groups, can affect their lives. The aim of this study was to investigate the relationship between mental health and perceived social support in the elderly referred to selected hospitals of Shahid Beheshti University of Medical Sciences in Tehran. Method: This study is a descriptive-correlational research that was performed in selected hospitals affiliated to Shahid Beheshti University of Medical Sciences in Tehran. The samples were the elderly referred to the mentioned hospitals who were included in the study by available sampling method and based on the inclusion and exclusion criteria from the study population. Data were collected through the "General Health Questionnaire"(GHQ-28) and the "Zimet Perceived Social Support Multidimensional Scale" and data analyzed using SPSS statistical package version 20. Results: The results showed that the mean of general health was 37.64( social dysfunction with an average of 10.30±4.24 and physical problems with an average of 10.23±4.54 were the most common psychological problems in the elderly)and perceived social support was 54.56, which indicates that the elderly have moderate mental health and perception of social support. Findings also indicated that there is an inverse and significant relationship between mental health and perceived social support of the elderly (r = 0.624). In other words, the lower a person’s perception of social support is associated with the greater risk to their mental health. Conclusions: The results showed that social dysfunction and physical problems(two subscales of general health) had been the most common psychological problems in the elderly. In addition, perceived social support from family, friends, and others in the elderly has been moderate. Therefore, the mental health of the elderly should be considered and awareness of families and other people involved with the elderly should be given priority for stronger emotional ties with the elderly and increase of social support. Keywords: Mental health, Perceived social support, the Elderly.